Micro Waqf Bank in Indonesia: Analysis of The Constitution Concept According to The Maqashid Sharia - Nugroho, Wahyu; Hilal, Faridl Noor (AL-IKTISAB: Journal of Islamic Economic Law, 2019)
Waqf is a legal act of wakif (endower) for separating and transferring part of their wealth either permanently or for a specified period in accordance with their interests for purposes of worship and the general welfare according to sharia. Islamic law have two characters, it is normative (muhkamat) so that Islam have a unity of mind, feeling, and behavior for the people and make the people united, and temporal (mutashabihat) to open up the difference by space, time, and the condition of each with regard to the purposes of syara’. Waqf is a legal act of wakif (endower) for separating and/or transferring part of their wealth either permanently or for a specified period in accordance with their interests for purposes of worship and/or the general welfare according to sharia. Waqf or endowments often directed to unmovable objects, while waqf on moving objects is being developed lately. The idea to explore and develop the concept of waqf in Indonesia was began when Mustafa Edwin Nasution translating paper written by M. Abdul Mannan that revealed the practice of cash waqf (SIBL) in Bangladesh. The government try to do innovation in order to boost the Muslim’s Economy particularly for those who are considered as a poor. The role of shariah bank and BWI and regulations is also considered ineffective, then the Government innovate by establishing institution called Micro Waqf Bank. Micro Waqf Bank is believed to increase financial inclusion, particularly in the public and small and micro businesses (SMEs) to have the easy capital. These agency is not allowed to take deposits from the public because it has focused in communities empowerment through financing with business mentoring.